2020
DOI: 10.1242/jcs.244624
|View full text |Cite
|
Sign up to set email alerts
|

Invariant chain regulates endosomal fusion and maturation through an interaction with the SNARE Vti1b

Abstract: The Invariant chain (Ii, CD74) is a multifunctional regulator of adaptive immune responses and responsible for sorting MHC-I, MHC-II and other Ii-associated molecules to a specific endosomal pathway. When Ii is expressed, endosomal maturation and proteolytic degradation of proteins are delayed and in non-antigen presenting cells the endosomal size increase, but he molecular mechanisms are not known. We identified that a SNARE, Vti1b, is essential for regulating these Ii induced effects. Vti1b binds to Ii and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 80 publications
(121 reference statements)
3
9
0
Order By: Relevance
“…In immune cells, Vti1b has been reported to play a role in lytic granule exocytosis in cytotoxic T cells ( Dressel et al, 2010 ). In addition, it has recently been suggested that Vti1b interacts with the invariant chain of the major histocompatibility complex II (MHCII) and directs the specific membrane fusion events in the early endosomal pathway that allow efficient antigen processing and antigen loading on MHCII ( Margiotta et al, 2021 ). However, no studies have been carried out on Vti1b in B cells.…”
Section: Introductionmentioning
confidence: 99%
“…In immune cells, Vti1b has been reported to play a role in lytic granule exocytosis in cytotoxic T cells ( Dressel et al, 2010 ). In addition, it has recently been suggested that Vti1b interacts with the invariant chain of the major histocompatibility complex II (MHCII) and directs the specific membrane fusion events in the early endosomal pathway that allow efficient antigen processing and antigen loading on MHCII ( Margiotta et al, 2021 ). However, no studies have been carried out on Vti1b in B cells.…”
Section: Introductionmentioning
confidence: 99%
“…With the extension of incubation time, green fluorescence was overflowed from red lysotracker at 8 h, indicating that these NPs escaped from endo/lysosomes, which was important for SV to exert its adjuvant effect. It is well known that Rab5 expressed early endosomes mature through acidification and material exchange to form Rab7a expressed late endosomes 43 , 44 . After treatment with AuNCs/TDPAs and AuNCs/SV/TDPAs, the expression of Rab5 and Rab7a were observed by CLSM.…”
Section: Resultsmentioning
confidence: 99%
“…To this regard, it is interesting to note that we identified in the interactome of T6BP, ATP6V0A1 a subunit of the vATPase that plays a critical role in mediating vesicular acidification (Forgac, 2007). On the other hand, CD74 has been shown to play, by itself, a role in endosomal membrane trafficking (Margiotta et al , 2020; Romagnoli et al , 1993) and perhaps in proteolysis of antigens (Schröder, 2016). It was recently reported that CD74 p41 isoform interacts with cathepsins and regulates their activity in endosomes (Bruchez et al , 2020).…”
Section: Discussionmentioning
confidence: 99%